Increased risk of atrial fibrillation in patients with inflammatory bowel disease: A nationwide population-based study - Choi, You-Jung (World J Gastroenterol, 2019)
BACKGROUND: Inflammatory bowel disease (IBD), a chronic inflammatory disease of the gastrointestinal tract, could play a role in the pathophysiology of atrial fibrillation (AF). AIM: To investigate the association between IBD and AF development. METHODS: We performed a population-based cohort study using records in the Korean National Health Insurance Services database between 2010 and 2014. A total of 37696 patients with IBD (12349 with Crohn’s disease and 25397 with ulcerative colitis) were identified. The incidence rate of newly diagnosed AF in patients with IBD was compared with that in a 3 times larger cohort of 113088 age- and sex-matched controls without IBD. RESULTS: During 4.9 ± 1.3 years of follow-up, 1120 patients newly diagnosed with AF (348 in the IBD group and 772 in controls) were identified. After adjustments using multivariable Cox proportional hazards, patients with IBD were at a 36% [95% confidence interval (CI) 20%-54%] higher risk of AF than controls. The association between IBD and the development of AF was stronger in younger than in older patients. Patients without cardiovascular risk factors showed a higher risk of AF primarily. Additionally, patients receiving immun-omodulators [Hazard ration (HR) 1.46, 95%CI 1.31-1.89], systemic corticosteroids (HR 1.37, 95%CI 1.10-1.71), or biologics agents (HR 2.38, 95%CI 1.51-3.75) were at higher risk of AF than patients without them. CONCLUSION: IBD significantly increased the risk of AF, and the impact of IBD on developing AF was in patients with moderate to severe disease.